Divident initiation of Singapore Initial Public Offering (IPO) firms (1990 - 2002) - Huang, Eugene Wei Jie (2008)
This paper investigates the dynamics of dividend initiation of IPO firms (1990 – 2002) in Singapore. We follow a sample of firms from their IPO, and using a multiple regression model, examine which firm characteristics are important in predicting dividend initiations. Two main theories have been drawn around dividend initiation. The first theory provides a signaling rationale for dividends in which dividend initiations are associated with higher earnings. The second theory provides a growth and investment opportunity rationale for dividend initiations. This prompted some market observers to believe that firms that do not initiate dividends have better growth prospects. This contradicts the Signaling theory. Due to these competing explanations, we attempt to determine which alternative theory on dividend initiations are applicable in this era and in the local context. Primarily, our results contradict the implication of signaling theory that increases in dividend rate is positively related to future firm prosperity. On the other hand, we find that the opposite argument of signaling theory (i.e. growth opportunities) does hold for our study. This is consistent with recent findings on dividend initiations that appear to reject Signaling Theory.